2020
DOI: 10.1186/s12913-020-05115-7
|View full text |Cite
|
Sign up to set email alerts
|

Valuing the cost of improving Chilean primary vaccination: a cost minimization analysis of a hexavalent vaccine

Abstract: Background: The phased withdrawal of oral polio vaccine (OPV) and the introduction of inactivated poliovirus vaccine (IPV) is central to the polio 'end-game' strategy. Methods: We analyzed the cost implications in Chile of a switch from the vaccination scheme consisting of a pentavalent vaccine with whole-cell pertussis component (wP) plus IPV/OPV vaccines to a scheme with a hexavalent vaccine with acellular pertussis component (aP) and IPV (Hexaxim®) from a societal perspective. Cost data were collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
(25 reference statements)
1
4
1
1
Order By: Relevance
“…It analyzed the costs from a societal perspective. Reports revealed that the total cost was reduced, consistent with the results seen in this study [ 18 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It analyzed the costs from a societal perspective. Reports revealed that the total cost was reduced, consistent with the results seen in this study [ 18 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…These findings were the incentives to investigate more in depth the rates of infection of pentavalent vaccines to be reconstituted versus the hexavalent vaccine that is ready to be used and estimate their cost difference. Studies on the economic value of the hexavalent vaccine suggested the following costs to be assessed: cost of the vaccine, cost of inpatient and/or outpatient visits, delivery cost, time cost, labor cost, cost for immunization errors and adverse events, and waste cost [ 18 , 19 , 20 , 21 ]. Our study adds the cost of infection contamination following immunization using the results of a model construct.…”
Section: Introductionmentioning
confidence: 99%
“…La vacuna hexavalente aP + IPV pasó a ser utilizada en la serie básica y para el primero refuerzo (2, 4, 6 y 18 meses). A pesar de su mayor costo directo en comparación con el esquema anterior, datos de un estudio reciente reportan una minimización teórica de este costo en diferentes escenarios al considerar los eventos adversos, almacenamiento y transporte, frente al cambio de la vacuna 38 . Además, el nuevo esquema de vacunas con una sola inyección fue encontrado altamente satisfactorio por los padres, con mínima disrupción en la vida diaria de sus progenitores, de los lactantes vacunados y del resto de los niños en el hogar 39 .…”
Section: Chileunclassified
“…Currently, there are limited studies on the economic evaluation of the combined DTaP‐based vaccines. Three studies performed economic analyses of the combined hexvalent DTaP‐IPV‐HepB‐Hib vaccine 21–23 . No combined DTaP‐IPV‐Hib vaccine economic evaluation has been reported in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Still, when all factors were considered in the study, the current scheme and the alternative ones exhibited obviously reduced difference in full-term infants.The CMA considered the social costs from a wider perspective, finding the ability of the alternative schemes to save the transportation and work loss costs of parents to bring their children for vaccination, and the total cost saving reaches 63.6%, 18.2%, and 36.4%, relative to the current scheme. A similar CMA was conducted on the introduction of hexavalent vaccine in South Africa, finding the strong necessity to implement the hexavalent vaccine in South Africa 21. It simplifies delivery and logistics infrastructure and reduces clinic visits, vaccination errors, the injection number as well as the side effects, thereby saving the costs of HCPs.…”
mentioning
confidence: 99%